2005
DOI: 10.1158/1078-0432.ccr-04-1988
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Response to Methotrexate, Vinblastine, Doxorubicin, and Cisplatin Neoadjuvant Chemotherapy for Bladder Cancers through Genome-Wide Gene Expression Profiling

Abstract: Purpose: Neoadjuvant chemotherapy for invasive bladder cancer, involving a regimen of methotrexate, vinblastine, doxorubicin, and cisplatin (M-VAC), can improve the resectability of larger neoplasms for some patients and offer a better prognosis. However, some suffer severe adverse drug reactions without any effect, and no method yet exists for predicting the response of an individual patient to chemotherapy. Our purpose in this study is to establish a method for predicting response to the M-VAC therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(122 citation statements)
references
References 32 publications
1
120
0
1
Order By: Relevance
“…Xue et al have recently reported that CD147 immunoexpression is as an independent prognostic factor for bladder cancer patients, playing an important role in tumour progression [14]. Takata et al identified, in non-responder patients with invasive bladder cancer treated by M-VAC regimen, a gene (SLC16A3) that is closely associated with CD147 [9]. Als et al identified CD147 as a strong independent prognostic factor for response and survival M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xue et al have recently reported that CD147 immunoexpression is as an independent prognostic factor for bladder cancer patients, playing an important role in tumour progression [14]. Takata et al identified, in non-responder patients with invasive bladder cancer treated by M-VAC regimen, a gene (SLC16A3) that is closely associated with CD147 [9]. Als et al identified CD147 as a strong independent prognostic factor for response and survival M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of UBC may be improved if we understand the molecular events that occur in tumour progression, identifying potential targets to, ultimately, achieve "personalized therapy". In this line of investigation, Takata and colleagues [9] observed that SLC16A3 (solute carrier family 16 -monocarboxylic acid transporter 4 -MCT4, member 3) is up-regulated in patients that do not respond to neoadjuvant M-VAC (methotrexate, vinblastine, doxorubicin and cisplatin) therapy. SLC16A3 (MCT4) is closely associated with CD147 [10], a highly glycosylated cell surface transmembrane protein which stimulates matrix metalloproteinases synthesis and angiogenesis in tumour local environment [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the levels of upregulation of UHRF1 in bladder tumours were much higher than that in kidney tumours (Po0.0001), suggesting that UHRF1 might be a sensitive tool for detection of bladder tumours, especially the upper tract TCCs, which are currently often found in advanced stages. Overexpression of UHRF1 was further confirmed in bladder tumours from 36 Japanese patients by microarray analysis (Takata et al, 2005(Takata et al, , 2007. Expression of UHRF1 in these bladder tumours was compared with the corresponding adjacent normal tissues from the same patients, and tumour/normal ratio was obtained.…”
Section: Immunohistochemical Staining Analysismentioning
confidence: 94%
“…After amplified RNAs (aRNAs) were labeled with Cy3 or Cy5, respectively, we carried out hybridization between labeled aRNAs and cDNA microarray slides containing 36 864 spots and detected the signals. Expression of CDC20 in various cancer tissues and their corresponding normal tissues were examined by using data sets that were analysed previously (Ono et al, 2000;Kitahara et al, 2001;Okabe et al, 2001;Hasegawa et al, 2002;Kaneta et al, 2002;Kitahara et al, 2002;Nagayama et al, 2002;Okutsu et al, 2002;Kikuchi et al, 2003;Okada et al, 2003;Ashida et al, 2004;Jinawath et al, 2004;Nakamura et al, 2004;Nishidate et al, 2004;Ochi et al, 2004;Obama et al, 2005;Takata et al, 2005;Hirota et al, 2006;Taniwaki et al, 2006;Yamabuki et al, 2006). To select genes that were suppressed by p53 and upregulated in various cancer tissues, the following two criteria were used: (1) genes whose expression were more than threefold decreased by Ad-p53 and (2) genes whose expression were more than threefold increased in various cancer tissues compared with its corresponding normal tissues.…”
Section: Cdna Microarraysmentioning
confidence: 99%
“…Extracted RNAs were reverse-transcribed using oligo(dT) 12-18 primer and SuperScript II reverse transcriptase (Invitrogen, Carlsbad, CA, USA). cDNAs of colorectal and bladder cancer tissues were prepared as described previously Takata et al, 2005). CDC20 was quantified by real-time RT-PCR that was performed in an Applied Biosystems 7700 sequence detector system with SYBR Premix Ex Taq (Takara, Tokyo, Japan).…”
Section: Rt-pcrmentioning
confidence: 99%